Energy Efficiency of Cooling Load through The Glass Facade of Office Buildings in Surabaya - Ulil Albab; Tri Joko Wahyu Adi (IPTEK Journal of Proceedings Series, 2019)
The aims of this article is to obtain an alternative type of glass on the envelope buildings of full glass on all surface envelope, cost of glazed facades and to obtain energy efficiency of cooling load through the glass facade of office buildings in Surabaya. The shape of the building in this article uses a simulation of regular form (squares) and differences in building orientation. The calculation method is uses the OTTV method (Overall Thermal Transfer Value) for the value of heat gain through the building envelope and the CLTD method (Cooling Load Temperature Difference) to calculate the cooling load affected by the glass facade. The results obtained in this article simulation show that the most efficient value is double glazing with using SC ≤ 1.9 and U value glass ≤ 2.6 W / m2K, so that the energy efficiency of the cooling load obtained can decrease until 6%. The savings were obtained at the value of OTTV is 25.60 W/m2 with the price of glass facade in the amount of Rp. 4,005,333/m2